OPTIMALISASI METODE PENDISKRIPSIAN BATUGAMPING UNTUK KARAKTERISASI RESERVOAR HIDROKARBON DALAM PEMODELAN GEOLOGI - -, Premonowati (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
Core/SWC and/or cuttings data from carbonate reservoir have to optimalized in their descriptions, actually for understanding their carbonate characterization. The cha-racterization is includes lithofacies and visible porosity. The method are consists of: core recovery, texture, orga-nism abundance, specific features, type and porosity percentage that have resulted a visible porosity. The precise calculation of visible porosity and factors of pore forming are best way to get a cementation factor which easily changes both ver-tical and horizontally. The carbonate depo-sitional facies and diagenetic process are use-ful to get a diagenetic unit that confirmed by cemen-tation process.